The Browsable Classroom: An Introduction to E-Learning for Librarians. - Beth A. Roberts (Issues in Science and Technology Librarianship, 2002)
The article reviews the book The Browsable Classroom: An Introduction to E-Learning for Librarians. New York: Neal-Schuman Publishers, 2002 by Linda W. Braun and Carolyn Noah.